The Implementation of Students’ Critical Thinking Toward Speaking Skill in an EFL Classroom - Tania Alfie Melani; Hanif Nurcholish Adiantika; Dila Charisma (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Muhammadiyah Cirebon, 2022)
The present study aims to investigate the implementation of critical thinking along with its advantage and disadvantage in EFL context. This study employs qualitative research by using case study design. This study was carried out in one vocational school in Cirebon, West Java, Indonesia. 6 (Six) students and one teacher were selected as the participants in this study. Interviews and observations were utilized as the instruments in this study. The findings indicate that critical thinking is thoroughly implemented through several cognitive level as proposed by Bloom’s classification. Furthermore, this study also shows several advantages and disadvantages of critical thinking for both students and teacher in EFL context. Therefore, it can be inferred that critical thinking offers several advantages for students and teacher despite its minor disadvantage in EFL classroom.